Proceedings of the 14th International Scientific Conference: Computer Aided Engineering - Rusiński, Eugeniusz; Pietrusiak, Damian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the proceedings of the 14th International Conference on Computer Aided Engineering, collecting the best papers from the event, which was held in Wrocław, Poland in June 2018. It includes contributions from researchers in computer engineering addressing the applied science and development of the industry and offering up-to-date information on the development of the key technologies in technology transfer. It is divided into the following thematic sections: • parametric and concurrent design, • advanced numerical simulations of physical systems, • integration of CAD/CAE systems for machine design, • presentation of professional CAD and CAE systems, • presentation of the modern methods of machine testing, • presentation of practical CAD/CAM/CAE applications: - designing and manufacturing of machines and technical systems, - durability prediction, repairs and retrofitting of power equipment, - strength and thermodynamic analyses of power equipment, - design and calculation of various types of load-carrying structures, - numerical methods of dimensioning materials handling and long-distance transport equipment (cranes, gantries, automotive, rail, air, space and other special vehicles and earth-moving machinery), • CAE integration problems. The conference and its proceedings offer a major interdisciplinary forum for researchers and engineers in innovative studies and advances in this dynamic field.
Design and Manufacture of Machines and Technical Systems -- Durability Prediction -- Repairs and Retrofitting of Power Equipment -- Strength and Thermodynamic Analysis for Power Equipment -- Design and Calculation of Various Types of Load-carrying Structures -- Numerical Methods for Dimensioning Materials Handling -- Long-distance Transport Equipment.
Keywords: Computer-aided engineering; Engineering design; Manufactures; Machinery; Electric power production; Computer-Aided Engineering (CAD, CAE) and Design; Engineering Design; Machines, Tools, Processes; Machinery and Machine Elements; Electrical Power Engineering